Are finance constraints hindering the growth of SMEs in Europe? - Rien Wagenvoort (EIB Papers, 2003)
This paper examines whether small and medium-sized enterprises (SMEs) in Europe suffer from a structural financing problem that hinders their growth. To this end, we estimate growth-cashflow sensitivities for firms in different size classes. Our results show that the sensitivity of company growth to cashflow rises as company size falls, which suggests that SMEs indeed encountered finance constraints that prevented them from fully exploiting their growth potential during the sample period 1996-2000. However, within each size class, quoted firms - even when small - tend to suffer less from finance constraints than unquoted firms.
Keywords: 330; Klein- und Mittelunternehmen; Unternehmensfinanzierung; Unternehmenswachstum; EU-Staaten